2010
DOI: 10.1177/1932202x1002100304
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Unexpected: Outlier Analyses of Factors Affecting Student Achievement

Abstract: In this study, we predicted achievement based on a variety of school demographic and background variables and identified schools that had achievement profiles that exceeded or fell short of their expected achievement levels. We identified schools that were over-or underper-forming and surveyed parents, teachers, and administrators in an effort to isolate factors that differ across the two types of schools. Across the three sets of surveys, perceptions of parents and perceptions about parents emerged as an inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 21 publications
1
30
0
2
Order By: Relevance
“…Researchers have noted this is a particularly important area for culturally diverse populadons (Reinke, Herman, Petras, & Ialongo, 2008;Walker et al, 2011). Other research, which was previously discussed, also documented that a positive perception of parents on the part of teachers was a key characteristic of highachieving low-income schools (McCoach et al, 2010). Other research, which was previously discussed, also documented that a positive perception of parents on the part of teachers was a key characteristic of highachieving low-income schools (McCoach et al, 2010).…”
Section: Influences On Contact and Comfortmentioning
confidence: 95%
See 2 more Smart Citations
“…Researchers have noted this is a particularly important area for culturally diverse populadons (Reinke, Herman, Petras, & Ialongo, 2008;Walker et al, 2011). Other research, which was previously discussed, also documented that a positive perception of parents on the part of teachers was a key characteristic of highachieving low-income schools (McCoach et al, 2010). Other research, which was previously discussed, also documented that a positive perception of parents on the part of teachers was a key characteristic of highachieving low-income schools (McCoach et al, 2010).…”
Section: Influences On Contact and Comfortmentioning
confidence: 95%
“…In one recent study, teacher perceptions of the two dimensions of contact and comfort were highlighted as potential contributing factors to children's success (McCoach et al, 2010). For instance, it is conceivable that some parents may be characterized as having low contact with schools but still be perceived as having a comfortable relationship; likewise, some parents may have firequent contact with teachers but be perceived as intrusive and unhelpful.…”
Section: Parent Involvement: Teacher Perceptions Of Contact and Comfortmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Jones and Zambone (2009) declare that ""… a supportive home environment; learned intelligence; and sufficient background knowledge and experience"" (p.236) are dynamics which fall under the student level. Contrary to this, McCoach, Goldstein, Behuniak, Reis, Black, Sullivan and Rambo (2010) regarded characteristics related to the learners" background, such as language, socioeconomic status and ethnicity as predictors of academic achievement. In this particular research study, the main factors at student level include social background, socioeconomic status and parental involvement.…”
Section: Conceptual Frameworkmentioning
confidence: 96%
“…The quality of education remains top priority of research and long been interested in exploring predictors contributing effectively related to students, parents, teachers and schools (Mushtaq & Nawaz Khan, 2012;Farooq, Chaudhry, Shafiq, & Berhanu, 2011;McCoach et al, 2010;Salami, 2008;Sackey, 2007;Barnard, 2004;Jeynes, 2003). On the other hand, researches on academic achievement concluded that school level effects is less important than student level, i.e., no consistent relationship exists between school characteristics and academic achievement (Shera, 2014).…”
Section: Introductionmentioning
confidence: 99%